Plant Phenology And Itsrelation TO The Cool Semi-Arid Conditions OF Sana'a - Abulfatih, H. A.; Al-Ani, M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In the cool semi-arid highland areas of Sana'a, a plantphonological study of forty two species revealed that there was onemajor outburst of plant emergence corresponding with the first periodof the heavy rainfall which take place during March-April. The secondperiod of heavy rainfall which takes place during July-August showsmoderate effect on emergence and growth.Plant Species included annuals, biennials and perennials. Perennialsshowedthefollowinggrowthformshemicryptophytes,chamaephytes, phanerophytes, and cryptophytes. Most plants whereherbaceous and a few where woodyDifferent Individuals of the same species could behave as annuals,biennials or perennials. In areas where soil moisture lasted for a shortperiod, plants behaved annuals, and in areas where moisture lasted forlonger periods, the plants behaved as biennials or perennials. Theprolonged period of leafing, flowering and fruiting experience by mostspecies also was caused by the moderate temperature which prevailedduring the yearLeafing, flowering and fruiting periods varied among species.However, they prevailed from March to November. Growth of most